1999
DOI: 10.1046/j.1365-3121.1999.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Active faults in the Sea of Marmara, western Turkey, imaged by seismic reflection profiles

Abstract: Turkey is moving westward relative to Eurasia, thereby accommodating the collision between Arabia and Eurasia. This motion is mostly taken up by strike‐slip deformation along the North and East Anatolian Faults. The Sea of Marmara lies over the direct westward continuation of the North Anatolian Fault zone. Just east of the Sea of Marmara, the North Anatolian Fault splits into three strands, two of which continue into the sea. While the locations of the faults are well constrained on land, it has not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 4 publications
3
79
0
4
Order By: Relevance
“…Its extreme youth (V2U10 5 a) stands in stark contrast to the much greater antiquity of the Marmara basins [13,42,44] and indicates that a signi¢cantly di¡er-ent mechanism must have formed the latter, before they were cut by the Main Marmara Fault about 2U10 5 a ago. There are also other active faults in the Sea of Marmara, mostly of normal type especially in the southern shelf area [45,46], whose relations to the Main Marmara Fault needs clari¢cation.…”
Section: The Relationship Of the Main Marmara Fault To Other Structurmentioning
confidence: 99%
“…Its extreme youth (V2U10 5 a) stands in stark contrast to the much greater antiquity of the Marmara basins [13,42,44] and indicates that a signi¢cantly di¡er-ent mechanism must have formed the latter, before they were cut by the Main Marmara Fault about 2U10 5 a ago. There are also other active faults in the Sea of Marmara, mostly of normal type especially in the southern shelf area [45,46], whose relations to the Main Marmara Fault needs clari¢cation.…”
Section: The Relationship Of the Main Marmara Fault To Other Structurmentioning
confidence: 99%
“…Also, the preferences for the solutions of the two possible planes (fault plane and auxiliary plane) were made by the tectonic properties and the knowledge of this region. Some studies show the existence of the normal faulting system in this area such as Parke et al (1999Parke et al ( , 2002 who mentions the basins that are half graben, formed on north dipping fault planes, in the southern Sea of Marmara by using regional grid of high-resolution seismic reflection profiles. They also reported that there is most likely a zone of deformation on the north of Marmara Island.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Those sediments are cut by north and south dipping faults with significant normal component of slip, as observed in high-resolution bathymetric maps Armijo et al, 2002;, deep-penetration seismic reflection and refraction data [Wong et al, 1995;Parke et al 1999;Carton et al, 2007;Laigle et al, 2008;Bécel et al, 2009; and 2-D and 3-D high resolution multichannel seismic data [Grall et al, 2012;Kurt et al, 2013]. At odds with the evidence for structural complexity and fault segmentation which appear to be fundamental features of the pull-apart system, Imren et al [2001; [2003] and Şengör et al [2005], among others, have alternatively interpreted the Marmara pull-apart system as a trough resulting mainly from the Western Anatolia N-S extensional regime during the middle Miocene.…”
Section: Geological Settingmentioning
confidence: 92%